Large external quality assessment survey on thrombin generation with CAT: further evidence for the usefulness of normalisation with an external reference plasma. Issue 1 (July 2015) - ; De Raucourt, Emmanuelle; Planche, Virginie; Ajzenberg, Nadine; Ollivier, Véronique; Helley, Dominique; Dignat-Georges, Françoise; Morange, Pierre; Drouet, Ludovic; Samama †, Michel-Meyer; Minon, Jean-Marc; et al.
Abstract: Background: Calibrated Automated Thrombography (CAT) has been widely used to assess in vitro thrombin generation as an informative intermediary phenotype of coagulation. Interlaboratory exercises have documented a worrisome poor reproducibility. There are some data on the normalisation with an appropriate external reference plasma (RP). This multicentre study of the French-speaking CAT Club aimed at providing further evidence for the usefulness of such a normalisation. Materials and Methods: Lyophilised aliquots of a RP along with 3 plasmas (P1 = normal; P2 = hypo-; P3 = hypercoagulable) were sent to 34 laboratories (corresponding to 38 instruments). CAT was studied using 1 and 5 pM tissue factor and other dedicated reagents. Normalisation with the local RP in use in the laboratory could also be performed. Interlaboratory CVs were calculated for each plasma before and after normalisation. Results: Regarding endogenous thrombin potential, a good discrimination between the 3 plasmas was achieved in all laboratories but there was no overlap after normalisation only. CVs were generally not reduced with the use of local RP but were generally improved with normalisation using the external RP, often becoming lower than 10%. Regarding P2 however, the benefit of normalisation was poor, and there were analytical difficulties as well, some laboratories being unable to get a useable signal. Conclusions: We confirm that normalisation of CAT results with a suitable external RP is useful in "real life" practice as it often permits an acceptable level of interlaboratory variability. In case of frank hypocoagulability, further improvements are required to get reliable, potentially clinically relevant results. Highlights: Normalisation with an external reference plasma generally reduces lab-to-lab variability Normalisation with the local reference plasma does not improve lab-to-lab variability Some parameters have still a great variability despite normalisation Further improvements are required, especially in case of frank hypocoagulability